Sinergi Kepemimpinan Demokratis dan Kompetensi Kepribadian Guru dalam Membentuk Karakter Disiplin Siswa Sekolah Dasar - Marlina Lena Hurint; Hermania Bhoki; Krisantus Minggu Kwen (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines efforts to improve fourth-grade students' disciplinary character through the implementation of principal's democratic leadership style and teacher personality competence at SDK Riangwulu, East Flores. Using a descriptive qualitative approach, the research was conducted over two weeks involving the principal, fourth-grade homeroom teacher, and fourth-grade students as research subjects. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed using an interactive analysis model. The results show that students' disciplinary character is in a good category across four indicators: compliance with school rules, compliance with learning activities, compliance in completing assignments, and neatness in wearing uniforms. The principal's democratic leadership style is implemented through consensus-based policies, high tolerance, creating a family atmosphere, and good communication. Teacher personality competence is reflected in the ability to be a role model, build positive relationships with students, and create authority through personality consistency. The main finding shows a positive synergy between the principal's democratic leadership and teacher personality competence that creates a conducive environment for forming students' disciplinary character. This research contributes theoretically to understanding systemic approaches in character education and provides practical implications for developing character formation strategies at the elementary education level.